The Role of Leadership In The Management of Family Planning Villages As A Family-Based Community Empowerment Strategy - Pertiwi, Putri Tsani; Dewi, Tisya Noptasya; Erawati, Dedet; Wulandari, Sri (Jurnal Polisci, 2025)
Background. The Indonesian government believes that the rapid population growth will have a significant impact on the country. The development program aims to improve the quality of life of the community. This quality of life includes various aspects related to prosperity and well-being. Aims. The purpose of this study is to identify and describe the role of leadership in managing KB Villages as a family-based community empowerment strategy in Balagedog Village, Sindangwangi District, Majalengka Regency. Methods. This study uses a qualitative descriptive approach. Data collection by conducting observations, interviews with primary informants and supporting informants, and documentation. This study utilizes leadership theory from Newstrom (2011), as cited in Wibowo (2018:5), with indicators including influence/support, voluntary effort, and goal achievement. Result. Based on the results of this study, the leadership role of the Family Planning Village in Balagedog Village, Sindangwangi District, Majalengka Regency has been running but is not optimal because several obstacles occur such as from several communities, especially in teenagers who are lacking and resulting in misperceptions of the family planning village program, approach strategies that have not been maximized, and lack of facilities and infrastructure. Conclusion. The researcher suggested that the approach strategy should pay more attention to the preparation and implementation of the family planning village program more maturely. Implementation. This will allow the community to understand accurately what is needed for the program, as well as the facilities and infrastructure that need to be improved